2012
DOI: 10.3109/0886022x.2012.708380
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between GSTM1/GSTT1 Null Genotypes and Renal Cell Carcinoma Risk: A Meta-Analysis

Abstract: The results from the published studies on the relationship between GSTM1/GSTT1 null genotypes and renal cell carcinoma (RCC) risk are still conflicting. This meta-analysis was performed to evaluate the relationship between GSTM1/GSTT1 null genotypes and RCC susceptibility. Association studies were identified from the databases of PubMed, Embase, Cochrane Library, and CBM-disc (China Biological Medicine Database) on 1 February 2012, and eligible investigations from 1950 to 2012 were synthesized using meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
1
18
1
Order By: Relevance
“…These results were consistent with a recent meta-analysis study conducted by Liu et al [41] who analyzed the relevance between GSTM1 polymorphism and RCC risk. In addition, Cheng et al [42] also demonstrated the association between the GSTM1 and GSTT1 polymorphisms and RCC risk in a meta-analysis, but there were some difference in conclusions between their studies and ours. Four papers [24], [27], [32], [33] included in our study showed a dramatic increase in the number of RCC cases and controls and provided available genetic information; however, this information was lacking in Cheng’s studies [42].…”
Section: Discussioncontrasting
confidence: 53%
“…These results were consistent with a recent meta-analysis study conducted by Liu et al [41] who analyzed the relevance between GSTM1 polymorphism and RCC risk. In addition, Cheng et al [42] also demonstrated the association between the GSTM1 and GSTT1 polymorphisms and RCC risk in a meta-analysis, but there were some difference in conclusions between their studies and ours. Four papers [24], [27], [32], [33] included in our study showed a dramatic increase in the number of RCC cases and controls and provided available genetic information; however, this information was lacking in Cheng’s studies [42].…”
Section: Discussioncontrasting
confidence: 53%
“…It is conceivable that individuals with GSTT1 null genotype may become susceptible to chemical carcinogens and thus develop kinds of cancers at high risks. Recent studies have found that GSTT1 null genotype is strongly associated with susceptibility to a number of cancers, such as colorectal, renal and esophageal cancers (Wang et al, 2003;Xu et al, 2011;Cheng et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with GSTT1 null genotype are more susceptible to chemical carcinogens and thus have a higher risk of developing malignant tumors. Recent studies have found that GSTT1 null genotype is strongly associated with susceptibility to a number of cancers, such as colorectal, renal and esophageal cancers (Wang et al, 2003;Xu et al, 2011;Cheng et al, 2012). Many previous studies have been published to estimate the association between GSTT1 polymorphism and esophageal cancer RESEARCH ARTICLE…”
Section: Introductionmentioning
confidence: 99%
“…Several of the GST family subgroup genes, including GST mu 1 ( GSTM1 ), GST pi 1 ( GSTP1 ), and GST theta 1 ( GSTT1 ), are highly polymorphic (Loktionov et al, 2001). Sequence variation in these genes has also been associated with an increased or decreased risk for several cancers and chronic diseases, including colorectal cancer (Loktionov et al, 2001), esophageal cancer (Sharma et al, 2013), renal cell carcinoma (Cheng, You, & Zhou, 2012; Yang et al, 2013), acute leukemia (Ye & Song, 2005), prostate cancer (Harries, Stubbins, Forman, Howard, & Wolf, 1997; Kote-Jarai et al, 2001; Liu, Liu, Ran, Shang, & Li, 2013; Safarinejad, Shafiei, & Safarinejad, 2011; Taioli et al, 2011; Wei et al, 2013), type-2 diabetes mellitus (Dadbinpour, Sheikhha, Darbouy, & Afkhami-Ardekani, 2013; Ramprasath et al, 2011), asthma (Tamer et al, 2004), and neurodevelopmental disorders such as ASD (Buyske et al, 2006). The variants in GSTM1 and GSTT1 examined here are insertion-deletion polymorphisms, and the homozygous deletions or null genotypes indicate that activities or functionality of these genes are reduced or interrupted completely (Ye, Song, Higgins, Pharoah, & Danesh, 2006).…”
Section: Introductionmentioning
confidence: 99%